(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The current pandemic could have accelerated a change of the traditional paradigm about the secondary use of health data. The traditional one has been based on the faculty of the individuals about accepting or not that use of their health data through the main role of informed consent. The new paradigm considers the current value of that secondary use for the improvement of the health of community and its individuals, through the possibilities offered by Big Data and AI. Therefore, the need of a balance between individual rights and the common good is indispensable. Pseudonymization could be the way to find this balance.